Evaluative Devices as Learning Opportunities - Foth, Dennis L. (Canadian Journal of Higher Education, 1975)
Thirty-three third- and fourth-year university students reported their preferences for eight evaluative devices which they had suggested might be used in a course they were taking. Students were instructed to base their preferences on the learning opportunities afforded by the different devices. The four most preferred evaluative devices comprised a pool of options from which students were required to select and complete two in addition to writing a final examination. The results of both the initial preferences stage and the actual choices stage suggested that the majority of students viewed the preparation for in-class or take-home examinations as better learning opportunities than the preparations for writing a paper, a research proposal or an annotated bibliography, for presenting a seminar, and for bi-weekly quizzes or an oral examination.